Social Networking Spaces From Facebook to Twitter and Everything In Between A Step-by-Step Introduction to Social Networks for Beginners and Everyone Else - Kelsey, Todd. (Apress, 2010)
What the heck is Facebook? Twitter? Blogging? This book answers these questions and explains how to use a variety of social networking sites to keep in touch, stay in business, and have fun. This book covers the main social networking spaces, and introduces some of the ways people are enjoying them within a family or business context. It includes information on posting pictures, using add-ons, and working with Facebook and LinkedIn groups. It also covers the phenomenon of Twitter, including how it has grown and the road ahead. This book also covers how you can use the various networks together, such as sending a Twitter message that updates your Facebook status, or exporting your LinkedIn contact list and using it to invite people to Facebook. It also includes discussion of how to use social networks for both personal and business use, and how to keep them separate. How to use Facebook, Twitter, and other social networking sites for family, friends, and business How to make your sites talk to each other How to make the most of social networking and stay out of trouble